El pájaro bebedor como herramienta para generar aprendizaje por contradicción - Vera Valcárcel, Diego Fernando; Rodríguez, Diego Julián (Revista Científica, 2011)
Many scientists have tried to violate the second law of thermodynamics from building a machine that has been called perpetual motion. A hypothetical machine would be able to continue working forever, after an initial boost, without additional external power,theoretically impossible to build. Given the need in awakening the scientific spirit among students, created the possibility of a perpetual motion machine hypothetical educational and fun that generates interest in learning about physical phenomena and concepts, bringing them into the classroom to perceive what would happen if these are not met, through asking questions like: What if there were no gravity? "Float around? Learning and generating contradiction. For this reason we designed a perpetual motion machine that enabled this contradiction, the "Drinking Bird" or bird drinker turns out to be a machine close to generating this movement properly simulate what would happen if you do not fulfill the second law of thermodynamics leading to understand the phenomenon more clearly, to finally see their debut from a real experiment that contradicts its definition.